Legal Protection of Childern as Perpetrators of Criminal Acts of Obscenity - Mustika, Mega; Mau, Hedwig A; Ismed, Mohamad (CV. Publikasi Indonesia, 2024)
The child protection is a fundamental human right. Every child is entitled to survival, development, participation, and protection from crime and discrimination. Legal protection for children involved in criminal acts, such as molestation, is governed by Law Number 11 of 2012 on the Criminal Justice System. This research utilizes Law Enforcement Theory and Law Protection Theory, adopting a normative juridical approach supported by empirical data. The study begins with an analysis of relevant legal articles and includes primary data to support secondary legal materials. The analysis aims to provide a prescriptive study with interpretive analysis. The findings reveal that legal regulations for child molestation cases, as in Decision Number 2/Pid.Sus-Anak/2022/PN Jkt Brt, are based on Article 82 paragraph (1) jo Article 76 E of Law Number 17 of 2016 and Article 64 paragraph (1) of the Criminal Code. Protection for child offenders is outlined in Article 71 paragraph (4) of the Child Protection Law and Article 3 of the Juvenile Criminal Justice System Law, emphasizing humane treatment and access to legal aid.